Increasing student identity in preventing student aggressive behavior - Arga Dian Zera; Firman Firman; Yanuar Kiram (International Journal of Applied Counseling and Social Sciences, 2021)
The low self-identity of students causes aggressive behavior. The phenomenon of aggressive behavior is the act of attacking others directly or indirectly to hurt others both physically and psychologically. Aggressiveness among adolescents is increasing from year to year, based on data released by the Central Statistics Agency, in 2007 it was recorded that 3145 adolescents aged ? 18 years of age became criminals and continued to increase to 3280 in 2007, and 4123 in 2008. Self-identity is one of the factors that influence the emergence of aggressive behavior. The purpose of this study is to describe the self-identity of students at SMK Muhammadiyah 1 Padang City. This research uses descriptive analysis. The sample of this study was 114 students who were taken using purposive sampling technique. The instrument used was "Self-identity scale in preventing aggressiveness" with a reliability value of 0.881. The results showed that: (1) the aspect of Identity diffusion was in the medium category with a percentage of 67%; (2) Identity foreclosure aspects are in the medium category with a percentage of 39%; (3) the Identity aspect of the moratorium is in the low category with a percentage of 45%; and (4) Identity achievement is in the low category with a percentage of 41.2%. The results of the study generally show that the students' self-identity is in the medium category with a percentage of 71.1% and it needs to be improved in order to prevent aggressive behavior.